(untitled) (Castilla. Estudios de Literatura, 2016)
On being interviewed about his literary preferences, film director Pedro Almodóvar said: “I think Clarín must be a handy reference author. I have had the desire for a long time to turn one of his stories, “Doña Berta”, into a movie. I´ll make it some day”. This article explores the affinities of Almodóvar´s filmography with Clarín´s short novel, “Doña Berta” in light of the melodrama genre. The goal of this research is to pinpoint the common topics and characteristics that both authors take from melodrama to argue that their convergence is most clearly apparent in: the prominence of the characters´ emotions and the focus on their love conflicts; the strongly structured feminine approach with an emphasis on the remarkable role of mothers; a sentimentally intense language style; some sensationalized contents; the instrumentalization of empathy in order to move the reader/spectator´s feelings; the support for fragile characters; the use of fictional narratives as key constituent of individual identity; and finally, the past as an unresolved situation determining the present.